2021
DOI: 10.1002/adsc.202100463
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalyzed Three‐Component Cyanoalkylsulfonylation of 2,3‐Allenoic Acids, Sulfur Dioxide, and Cycloketone Oxime Esters: Access to Cyanoalkylsulfonylated Butenolides

Abstract: An iron‐catalyzed three‐component cyanoalkylsulfonylation of 2,3‐allenoic acids, K2S2O5, and the ring‐opening of cyclobutanone oxime esters is described. The radical tandem cyclization route allows access to diverse cyanoalkylsulfonylated butenolides in moderate to good yields under mild conditions. Moreover, the products are further converted, offering the corresponding derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 88 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…On the basis of the above experimental results and related literature reports, Scheme 6 gave a possible reaction mechanism [18] . Initially, ArCF 2 CO 2 H (ArSCF 2 CO 2 H, ArOCF 2 CO 2 H) 2 (4/6) was affected by persulfate, releasing a molecule of carbon dioxide, and persulfate itself disproportionated into sulfate and sulfate ions.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…On the basis of the above experimental results and related literature reports, Scheme 6 gave a possible reaction mechanism [18] . Initially, ArCF 2 CO 2 H (ArSCF 2 CO 2 H, ArOCF 2 CO 2 H) 2 (4/6) was affected by persulfate, releasing a molecule of carbon dioxide, and persulfate itself disproportionated into sulfate and sulfate ions.…”
Section: Resultsmentioning
confidence: 77%
“…On the basis of the above experimental results and related literature reports, Scheme 6 gave a possible reaction mechanism. [18] Initially, ArCF…”
Section: Resultsmentioning
confidence: 99%
“…[16] Over the past decades, three-component methodology utilizing handled convenient sulfur dioxide surrogate [17] for the installation of a sulfonyl group has received increasing attention. [18] Based on our previous work on radical cyclization, [19] herein we report visible-light-induced photocatalyst-free three-component difluoroamidosulfonylation of terminal alkynes and N-allylbromodifluoroacetamides with the insertion of sulfur dioxide.…”
mentioning
confidence: 99%
“…In recent years, by utilizing the sulfur dioxide insertion strategy, tremendous progress in the synthesis of sulfonyl compounds has been witnessed . So far, sulfur dioxide surrogates such as DABCO·(SO 2 ) 2 , potassium or sodium metabisulfite, rongalite, and thiourea dioxide have been widely utilized for various transformations to prepare sulfones. In particular, we and others have found that the radical-triggered insertion of sulfur dioxide represents an effective strategy for installing sulfonyl group into organic molecules. Among these approaches, the radical-involved vicinal difunctionalization of alkenes or alkynes through sulfur dioxide insertion has been demonstrated as a convenient method for generating alkyl or vinyl sulfones (Scheme a, top).…”
mentioning
confidence: 99%
“…Initially, we postulated that iminyl radical species A and Cu­(II) species would be generated through the interaction of cycloketone oxime ester 3a and the Cu­(I) species via a single-electron transfer (SET) process . Then, iminyl radical A would undergo a ring-opening process through β-C–C bond cleavage to produce cyanoalkyl radical B , which would be rapidly captured by sulfur dioxide from DABCO·(SO 2 ) 2 to provide the corresponding cyanoalkylsulfonyl radical C . The radical addition of intermediate C to 1,3-enyne 1a would afford propargyl radical D and its resonance form as allenyl radical species E . In this context, the chemoselective radical attack of the cyanoalkylsulfonyl moiety toward the alkene group instead the alkyne moiety might be attributed to the lower steric hindrance of the terminal alkene group.…”
mentioning
confidence: 99%